Studi Kualitatif Potensi Listrik: Konsep Dasar dan Aplikasinya dalam Kehidupan Sehari-Hari - Nurhaliza, Dwi (Maliki Interdisciplinary Journal, 2025)
Electric potential is one of the fundamental concepts in physics that plays an important role in various aspects of daily life. This study aims to analyze the basic concept of electric potential and its applications in everyday life through a qualitative approach. The theory and fundamentals of electric potential are explained and linked to practical examples in real life, such as household electrical systems, batteries and accumulators, medical technology, and renewable energy-based power generation. The research results show that a deep understanding of electric potential can improve energy efficiency and contribute to the development of safer and more sustainable electrical technology. Therefore, mastering this concept is essential, both in the academic realm and in daily life, to enhance awareness of wiser and more efficient electricity usage.